The Syro-Anatolian city-states: an Iron Age culture - Osborne, James F. ca. 20./21. Jh. (Oxford studies in the archaelogy of ancient states, 2020)
This book is the first to characterize the Iron Age city-states of southeastern Turkey and northern Syria, using archaeological, historical, and visual evidence to argue for a unified cultural formation characterized above all by diversity and mobility.